Rapid Daignostic Lateral Flow Strip Test Reader - Özkan, Haydar (Balkan Yayın, 2017)
Non-invasive rapid diagnostic tests (RDT) are commonly used to detect some kind of viruses or bacteria instead of invasive methods. Helicobacter pylori (H. Pylori) which causes gastric cancer, peptic ulcer, gastritis, mucosa-associated lymphoid tissue lymphoma diseases can be detected easily with lateral flow strip (LFS) that is one of the RDT types. The tests are evaluated whether there are control line and test line at the region of interest (ROI) by users or microbiology technicians manually. Once the test line is tentative, despite the test must be reported positive, it can be resulted as negative incorrectly. This incorrect diagnose causes incorrect treatment planning. In this work, to mitigate this problem which will be able to occur by human based, an automatic LFS-RDT reading system is developed. The computer laptop based system firstly takes image utilizing the holders that are designed with 3D printer. Whether the test have the control-test lines or not are carried out by image processing techniques straightforwardly. After feature extraction from line areas, k-NN classification method is used to evaluate the test results automatically. 100 LFS-RDTs are tested and observed that all results are correct. The system is found quite useful and approved as a second reader by medical technicians.
Keywords: Rapid Diagnostic Test Reader; Classification; k-NN; Image Processing